Efektivitas Towel Curl dan Core Stability terhadap Keseimbangan Dinamis pada Anak Flat foot: Sebuah Kajian SLR - Devina Alifya Ramadhanti; Pipin Suparmi (Yayasan Literasi Sains Indonesia, 2026)
Flat foot is a condition characterized by a reduction in the medial longitudinal arch that can affect dynamic balance. This condition has the potential to cause postural disturbances, reduced physical activity capacity, and an increased risk of future injury. This study aims to analyze the effectiveness of towel curl exercises and core stability exercises in improving dynamic balance in children with Flat foot using a Systematic Literature Review (SLR) method. The methods used adhere to the PRISMA guidelines. A literature search was conducted via Google Scholar and Scopus covering the publication years 2020–2025, resulting in 4 articles meeting the inclusion and exclusion criteria. The analysis revealed that both interventions—towel curl exercises and core stability exercises have a significant effect on improving intrinsic foot muscle strength, postural stability, and dynamic balance in children with Flat foot. The combination of both exercises yielded more optimal results compared to single exercises because it involves synergy between the leg muscles and the core muscles. Thus, it can be concluded that towel curl and core stability exercises are effective in improving dynamic balance in children with Flat foot.